Therapeutic potential of Opuntia ficus indica extract against cadmium-induced osteoporosis and DNA bone damage in male rats - Jihen Taleb; Saida Ncibi; Intidhar Bkhairia; Amani Smida; Lamia Mabrouki; Moncef Nasri; Lazhar Zourgui (Journal of Tropical Pharmacy and Chemistry, 2022)
The purpose of the present study was to assess the protective effects of ‘Opuntia ficus indica’ (family Cactaceae) against osteoporosis induced by cadmium chloride in female Wistar rats. Experiments were carried out on 36 male Wistar rats (6-8 weeks old) divided into four groups of nine each: a control group, a group treated with cadmium (3,5 mg/kg /day) by subcutaneous injection, a group treated with Opuntia ficus indica extract (100 mg/Kg/day) by gavage, and a group treated with opuntia extract then treated with cadmium. After 10 weeks of treatment, animals from each group were rapidly sacri?ced by decapitation. Blood serum was obtained by centrifugation. Bone toxicity was estimated by examining femoral length and weight, calcium, phosphorus, vitamin D3 and alkaline phsphatase (ALP) levels, oxidative status and DNA aspects in femur tissue. Results showed that cadmium could induce hypocalcemia, hypophosphatemia, Vit D deficiency, increase in ALP level, and decrease in femur weight and length. Also, an oxidative stress evidenced by statistically signi?cant losses in the activities of catalase (CAT), superoxide-dismutase (SOD), glutathione-peroxidase (GPX) activities and an increase in lipids peroxidation level in bone tissue of cadmium-treated group compared with the control group. In addition, histological analysis in bone tissue of cadmium-induced rats revealed pronounced morphological alterations with areas of bone resorption and a loss of normal architecture of femur diaphysis bone as well as DNA fragmentation. However, administration of cactus extract attenuated cadmium-induced bone damage. The protective effect of the plant can be attributed to its antioxidant properties and the existence of phenolic acids and flavonoids, as highlighted by HPLC-based analysis. These findings indicate that ‘Opuntia ficus indica’ extract, can be used as a new option in nutraceutical field.